2018
DOI: 10.1007/s10006-018-0701-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complications and flap losses in mandibular reconstruction with microvascularized fibula flap

Abstract: The mandibular defects caused by mandibulectomies can involve esthetic and functional sequelae in patients. The fibula presents positive aspects and can be used as an option for mandibular reconstruction after tumor resections or extensive traumas. Furthermore, this retrospective study of the patients who have passed through a mandibular reconstruction with a microvascular fibular flap over the last 17 years describes the experience of the Oral and Maxillofacial SurgeryService at the ErastoGaertner Hospital, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In our third case we worked in collaboration with maxillofacial surgeons. In such procedures, a bone resorption can be observed in allografts, especially after radiotherapy in the postoperative period [ 55 ]. The plates used are not sufficiently strong and ultimate solutions for the temporomandibular joint cannot be found.…”
Section: Discussionmentioning
confidence: 99%
“…In our third case we worked in collaboration with maxillofacial surgeons. In such procedures, a bone resorption can be observed in allografts, especially after radiotherapy in the postoperative period [ 55 ]. The plates used are not sufficiently strong and ultimate solutions for the temporomandibular joint cannot be found.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a metaanalysis including 511 patients showed no differences in the use of these two systems of xation; however, clinical records showed that reconstruction plates were associated with both less complications and local exposure in the postoperative period than miniplates [21]. Parise et al retrospectively evaluated 43 patients submitted to mandibular reconstruction with free bular ap [22]. In the two cases in which system 2.4 reconstruction platers were used for xation, the plate was exposed to the oral cavity during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Flap failure appears in up to 13% in most reports. 2,7,10,[15][16][17][18] Operative outcome and complications are multifactorial and are patient and surgical team dependent. During the study period, we have found a statistically significant improvement in overall flap success rates with flap failure decreasing from 28% in early years to 8% in the recent decade.…”
Section: Discussionmentioning
confidence: 99%
“…Flap failure rates range between 0 and 13% in the majority of reports. 2,7,10,[15][16][17][18] During our 21-year experience with the FFF for head and neck reconstruction, we have performed several key changes in presurgical planning, surgical technique, and postoperative monitoring. The aim of this study was to describe the demographics, operative, and postoperative course of this cohort of patients, describe the changes we performed in our practice and assess trends in outcome.…”
mentioning
confidence: 99%